β3GnT8 Promotes Colorectal Cancer Cells Invasion via CD147/MMP2/Galectin3 Axis - Jiang, Zhi; Zhang, Huan; Liu, Chunliang; Yin, Jun; Tong, Shan; Lv, Junxing; Wei, Shaohua; Wu, Shiliang (Frontiers in Physiology, 2018)
β1,3-N-Acetylglucosaminyltransferase (β3GnT8) and β3GnT2 are key enzymes that catalyzes the formation of polylactosamine glycan structures by transferring GlcNAc to tetre-antennary β1-6-branched N-glycan and it also has an important effect on the progression of various types of human cancer. They have been reported to participate in tumor invasion and metastasis by regulating the expression of matrix metalloproteinases (MMPs), CD147 and polylactosamine. However, whether β3GnT8 and β3GnT2 play a role in colorectal cancer and, if so, the underlying mechanisms remain unclear. In our study, we detected the expression of β3GnT8, CD147, MMP2, and galectin3 by immunohistochemistry on 90 paraffin-embedded slices. We found that β3GnT8, CD147, MMP2, and galectin3 were over-expressed in colorectal cancer tissues. Overexpression of β3GnT8 promoted invasion of colorectal cancer cells, whereas knockdown of β3GnT8 and β3GnT2 inhibited the invasive activity. Mechanistically, β3GnT8 and β3GnT2 modulated the glycosylation patterns of CD147 and altered the polylactosamine structures in colorectal cancer cells. Together, these results illustrate that the novel role and the molecular mechanism of β3GnT8 and β3GnT2 in promotion of colorectal cancer invasion. These results suggest that targeting β3GnT8 may be a potential therapeutic strategy against colorectal cancer.